A hypoxia-specific and mitochondria-targeted anticancer theranostic agent with high selectivity for cancer cells. Issue 16 (16th April 2018) - Hu, Mingxing; Yang, Chao; Luo, Yi; Chen, Fan; Yang, Fangfang; Yang, Shuping; Chen, Hao; Cheng, Zhiqiang; Li, Kun; Xie, Yongmei
Abstract : A novel hypoxia-specific and mitochondria-targeted theranostic agent, HMX-1, was reported with certified anti-cancer efficiency in vitro and in vivo . Abstract : Herein, a novel soluble mitochondria-targeted theranostic compound, HMX-1, was presented, which was selectively activated under hypoxia with excellent mitochondria-targeting ability at the cellular level, accompanied by a dramatic increase in the fluorescence intensity. Moreover, its anti-cancer efficiency was certified both in vitro and in vivo .